Osteotomy for Sigmoid Notch Obliquity and Ulnar Positive Variance - Dickson, Lisa M.; Tham, Stephen K. Y. (Journal of Wrist Surgery, 2014)
Background Several causes of ulnar wrist pain have been described. One uncommon cause is ulnar carpal abutment associated with a notable distally facing sigmoid notch (reverse obliquity). Such an abnormality cannot be treated with ulnar shortening alone because it will result in incongruity of the distal radioulnar joint (DRUJ).Case Description A 23-year-old woman presented with ulnar wrist pain aggravated by forearm rotation. Ten years earlier she had sustained a distal radius fracture that was conservatively treated. Examination revealed mild tenderness at the DRUJ and decreased wrist flexion and grip strength on the affected side. Radiographic examination demonstrated 1 cm ulnar positive variance, ulnar styloid nonunion, and a 37° reverse obliquity of the sigmoid notch. The patient was treated with ulnar shortening and rotation sigmoid notch osteotomy to realign the sigmoid notch with the ulnar head.Literature Review Sigmoid notch incongruity is one of several causes of wrist pain after distal radius fracture. Traditional salvage options for DRUJ arthritis may result in loss of grip strength, painful ulnar shaft instability, or reossification and are not acceptable options in the young patient. Sigmoid notch osteotomy or osteoplasty have been described to correct the shape of the sigmoid notch in the axial plane.Clinical Relevance We report a coronal plane osteotomy of the sigmoid notch to treat reverse obliquity of the sigmoid notch associated with ulnar carpal abutment. The rotation osteotomy described is particularly useful for patients in whom a salvage procedure is not warranted.
Keywords: DRUJ; sigmoid notch; distal radius; DRUJ instability